Comparing the Efficiency of UV/TiO2 and UV/O3 Processes in Degradation of Sulfonamide Antibiotics in Aquatic Solution - Mahsa Tahergorabi; Mohammad Malakootian; Samaneh Dehghan; Ali Esrafili; Majid Kermani; Mojtaba Yegane Badi (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Emerging pollutants such as antibiotics are resistant to biodegradation. The aim of this study was to compare the effect of photocatalytic and Ozonation photolysis on decomposition of Sulfonamide antibiotics (Sulfacetamide, Sulfathiazole, Sulfamethoxazole, and Sulfadiazine) in aquatic environments. Materials and methods: In this study, experiments were conducted discontinuously. The effect of some parameters, including pH, initial antibiotic concentration, ozone concentration, contact time, and concentration of TiO2 on degradation of Sulfonamide antibiotic was investigated. Characteristics of this catalyst were analyzed using FTIR, XRD, SEM, and EDX techniques. The concentrations of antibiotics were measured by an HPLC analyzer equipped with a UV detector at a wavelength of 270 nm. Results: The highest percentage of sulfonamide removal under optimal conditions (pH 5, initial concentration of antibiotics= 10 mg/l, ozone concentration= 0.22 g/h, and catalyst concentration= 1 g/l) were obtained by photocatalytic and photolysis processes (92.1% and 100%, respectively). Intermediate products produced under these conditions included acetic acid, butyric acid, and low molecular weight products. TOC removal efficiencies of sulfonamides by photocatalytic and ozonation photolys were 80% and 79.6%, respectively. Conclusion: The study showed that the rate of ozonation photolysis reaction in the removal of sulfonamides was 2.6 times faster than the photocatalytic process.